Значення волонтерського підходу до педагогічного діяльності - Даріуш Скальські (Pavlo Tychyna Uman State Pedagogical University, 2014)
Статтю присвячено розгляду специфіки педагогічної роботи з урахуванням волонтерського підходу. Автор розглядає професію вчителя, наділяючи її атрибутами волонтерської діяльності, добровільністю, скерованою на користь іншої особи, емпатією, альтруїзмом. Педагогічна підготовка розглядається як процес, а педагогічна робота - як стан. Статья посвящена рассмотрению специфики педагогической деятельности с волонтёрского подхода. Автор рассматривает профессию учител; наделяя её атрибутами волонтёрской деятельности: добровольностью, нацеленной на пользу другим людям, эмпатией, альтруизмом. Педагогическая подготовка рассматривается как процесс, педагогическая деятельность - как состояние. The article uses voluntariate approach to teaching. The above mentioned approach was paid close attention to at (Brussels, 2011). The event was summarizing the main activities of 2011 which was pronounced the Year of Volunteering. First of all, the author gives the principle definitions of volunteering laying the emphasis on free will, awareness, empathy and altruism. He provides a number of proves to the fact that the teacher and the volunteer have much in common both relying on the above mentioned attributes. The next thing the author is drawing attention to the teacher as a unique personality who has knowledge, particular social and psychological characteristics. The author stresses that the person considering teaching as a career should have volunteers qualities. And finally, the author raises some issues for further discussions, dealing with voluntaries nature of teaching.